PELAKSANAAN WEWENANG MAHKAMAH KONSTITUSI DALAM MENGUJI UNDANG - UNDANG YANG DIUNDANGKAN SESESUDAH AMANDEMEN UUD 1945 - Sudirman Jabir (AkMen JURNAL ILMIAH, 2016)
The background of this research; Authority in testing the Constitutional Court Act which was enacted before the 1945 amendment; And How implementation of the authority of the Constitutional Court in examining the Act which was enacted before the 1945 amendments. This thesis research aims to: To determine the Constitutional Court and analyzing powers in examining legislation enacted before the 1945 amendments, and for knowing and analyzing How the implementation of the Constitutional Court the authority in testing the law that was enacted before the 1945 amendments. From the results of this research note that the Constitutional Court in implementing the Judicial review is limited to the Act after the 1945 changes, but with the cancellation of article 50 of Law No. 24 Year in 2003 by the Constitutional Court that none other than the law governing the Constitutional Court Act which can be requested to be tested is the Law which was enacted after the 1945 change, while the Constitutional Court the authority contained in Article 24C of the 1945 Constitution there are no restrictions in testing the Act, then the that the basis of article 50 of Law No. 24 Year 2003 is seen deviating from the Constitution in 1945. thus the Constitutional Court in accepting applications for the Act to be tested are not limited anymore to the Act which was enacted after the 1945 amendments. Based on the conclusion that the Supreme Kostitusi in testing law was enacted before the 1945 change is a constitutional authority. The reason of article 50 of Law No. 24 Year 2003 regarding the Constitutional Court Act which set restrictions on who should be tested against the Constitutional Court of Article 24C of the 1945 Constitution. Article 50 of Law No. testing. 24 Year in 2003 by the Supreme Constitutional Court can not be said to extend authorities but upholding the Constitutional Court (1945).